(untitled) (Research, Society and Development, 2022)
This work aims to determine the challenges in the process of implementing Building Information Modeling (BIM) in micro-enterprises in the Architecture, Engineering and Construction (AEC) sector. The methodology applied consisted of an exploratory approach, based on the survey of opinions of professionals working in the AEC sector, about the applicability and level of difficulty of the challenges in the process of implementing BIM to the reality of micro-enterprises. To survey opinions, it was used an online questionnaire prepared in accordance with the review of the technical-scientific literature on the subject. In the study, it was possible to identify and evaluate the level of difficulty of 41 challenges in the process of implementing BIM to the reality of micro-enterprises, showing that the lack of knowledge, on the part of business customers, about the advantages of BIM is the most critical among them. 13 challenges not mentioned in the existing literature were identified. Thus, by organizing, evaluating and categorizing the challenges, it is concluded that the development of an implementation plan, with strategies based on the challenges identified in this research, can help in the process of implementing BIM in micro-enterprises in the AEC sector.